Digital Business Model Innovation In SMEs: A Systematic Literature Review - Yerizal Yerizal; Vera Septaria (LP2M IAIN Palopo, 2025)
Purpose – Digital business model innovation (DBMI) is crucial for SMEs to survive and thrive in this era of rapid digital transformation. However, research on DBMI remains fragmented, with limited understanding of the driving factors, implementation strategies, impacts, and challenges faced by SMEs in adopting DBMI. This article systematically reviews the literature on DBMI in SMEs (2015-2025), identifying key themes, research gaps, and providing future research directions. Methodology –This study uses a systematic literature review (SLR) approach based on PRISMA guidelines. The selected literature consists of 25 articles that were analysed descriptively and thematically, with a focus on the SME context. Findings – The review results show that DBMI is influenced by internal factors such as transformational leadership and technological readiness, as well as external factors such as government support and crises. The implementation of DBMI in SMEs includes process digitization, value proposition innovation, and revenue model changes. The impacts include improved financial performance, competitiveness, and business resilience, despite challenges such as resource constraints and resistance to change. Originality – This article fills the literature gap by synthesizing DBMI in SMEs from developing countries and offers a new theoretical framework for digital business model development.